Improving the extraction of Ara h 6 (a peanut allergen) from a chocolate-based matrix for immunosensing detection: Influence of time, temperature and additives. (1st March 2017) - Alves, Rita C.; Pimentel, Filipa B.; Nouws, Henri P.A.; Silva, Túlio H.B.; Oliveira, M. Beatriz P.P.; Delerue-Matos, Cristina
Highlights: Extraction of Ara h 6 from a complex chocolate-based food matrix was optimized. 36 different conditions (regarding time, temperature and additives) were tested. The use of additives improved Ara h 6 extraction. Ara h 6 was highly extracted at 21 °C, during 60 min. Abstract: The extraction of Ara h 6 (a peanut allergen) from a complex chocolate-based food matrix was optimized by testing different temperatures, extraction times, and the influence of additives (NaCl and skimmed milk powder) in a total of 36 different conditions. Analyses were carried out using an electrochemical immunosensor. Three conditions were selected since they allowed the extraction of the highest levels of Ara h 6. These extractions were performed using 2 g of sample and 20 ml of Tris-HNO3 (pH = 8) containing: a) 0.1 M NaCl and 2 g of skimmed milk powder at 21 °C for 60 min; b) 1 M NaCl and 1 g of skimmed milk powder at 21 °C for 60 min; and c) 2 g of skimmed milk powder at 60 °C for 60 min. Recoveries were similar or higher than 94.7%. This work highlights the importance to adjust extraction procedures regarding the target analyte and food matrix components.